ANALISIS PEMBELAJARAN HIGH ORDER THINKING SKILL (HOTS) PADA MATERI DINAMIKA ATMOSFER DAN DAMPAKNYA TERHADAP KEHIDUPAN (STUDI DI SMAN 10 DAN SMAN 8 PADANG) - khrisna dewita; nofrion nofrion (JURNAL BUANA, 2019)
This article was written to find out the feasibility of HOTS learning in terms of planning aspects, implementation aspects, and learning assessment aspects in Basic Competency (KD) of Atmospheric Dynamics and Its Impact in Life. This type of research is descriptive research with a quantitative approach. The population of this research are all Class X IPS at SMAN 8 Padang and SMAN 10 Padang. The determination of the sample is done by random sampling technique. The sample chosen in this research is Class X IIS 1 for SMAN 10 Padang and X IPS 1 for SMAN 8 Padang. The result shows that in terms of lesson planning aspects at SMAN 8 Padang and SMAN 10 Padang are in very good category with a percentage of 89.58% - 95.83%. In terms of the implementation aspects of learning it results in advanced learning activities (ABL) with a percentage of 62.78% - 70.00% in deficient category, while at SMAN 10 Padang with a percentage of 90.32% - 91.29% in very good category. In terms of assessment aspects (students’ worksheet) which was made by teachers of SMAN 8 Padang with a percentage of 75% - 87.5% is in good category, while students’ worksheet made by teachers of SMAN 10 Padang with a percentage of 75% - 100% in very good category. Keywords: Feasibility, HOTS, Geography Learning, Basic Learning Activities, Advanced Learning Activities